Thinking Like a Lawyer Abroad: Putting Justice into Legal Reasoning - James R. Maxeiner (Washington University Global Studies Law Review, 2012)
Americans are taking new interest in legal reasoning. Thinking Like a Lawyer: A New Introduction to Legal Reasoning by Professor Frederick Schauer suggests why. According to Schauer, American legal methods often require decision-makers “to do something other than the right thing.” There has got to be a better way. Now comes a book that offers Americans opportunities to look into a world where legal methods help decision-makers do the right thing. According to Reinhard Zippelius in his newly translated Introduction to German Legal Methods, German legal methods help decision makers resolve legal problems “in a just and equitable manner.” This Article sets out what good legal methods do: help decide legal problems justly. It poses the puzzle: why does Schauer say legal methods challenge rather than support doing the right thing, when Zippelius does not? Relying on Schauer himself, the Article suggests an answer: neglect of legislation and law application and fixation on appellate law-making. It shows how German legal methods as described by Zippelius help decision makers to do the right thing.
Keywords: Frederick Schauer; Reinhard Zippelius; Legal ethics; lawyering